Elucidation of the Key Role of [Ru(bpy)3]2+ in Photocatalyzed RAFT Polymerization1. Issue 15 (11th May 2016) - Christmann, Julien; Ibrahim, Ahmad; Charlot, Vincent; Croutxé‐Barghorn, Céline; Ley, Christian; Allonas, Xavier
Abstract: Photocatalysis reactions using [Ru II (bpy)3 ] 2+ were studied on the example of visible‐light‐sensitized reversible addition–fragmentation chain transfer (RAFT) polymerization. Although both photoinduced electron‐ and energy‐transfer mechanisms are able to describe this interaction, no definitive experimental proof has been presented so far. This paper investigates the actual mechanism governing this reaction. A set of RAFT agents was selected, their redox potentials measured by cyclic voltammetry, and relaxed triplet energies calculated by quantum mechanics. Gibbs free‐energy values were calculated for both electron‐ and energy‐transfer mechanisms. Quenching rate constants were determined by laser flash photolysis. The results undoubtedly evidence the involvement of a photoinduced energy‐transfer reaction. Controlled photopolymerization experiments are discussed in the light of the primary photochemical process and photodissociation ability of RAFT agent triplet states. Abstract : Electron or energy transfer? Photocatalysis involving [Ru II (bpy)3 ] 2+ is generally described by an electron‐transfer mechanism. In contrast, detailed mechanistic investigations show that the interaction between [Ru(bpy)3 ] 2+ and reversible addition–fragmentation transfer (RAFT) agents is actually governed by energy transfer. Sensitized controlled polymerization of methyl acrylate supports this contention.